2017
DOI: 10.1038/ncomms16079
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA cluster miR-17-92 regulates multiple functionally related voltage-gated potassium channels in chronic neuropathic pain

Abstract: miR-17-92 is a microRNA cluster with six distinct members. Here, we show that the miR-17-92 cluster and its individual members modulate chronic neuropathic pain. All cluster members are persistently upregulated in primary sensory neurons after nerve injury. Overexpression of miR-18a, miR-19a, miR-19b and miR-92a cluster members elicits mechanical allodynia in rats, while their blockade alleviates mechanical allodynia in a rat model of neuropathic pain. Plausible targets for the miR-17-92 cluster include genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 54 publications
3
82
0
Order By: Relevance
“…[59][60][61] Recent experiments have shown that coexpressed miRNA clusters consisting of three to six members can regulate a specific molecular pathway by targeting the same signalling pathway. 13,14 The miR-183 cluster (bearing miR-183,miR-96, and miR-182) and the miR-17-92 cluster (bearing miR-17,miR-18a,miR-19a, miR-19b, and miR-92a) controlled neuropathic pain by repressing auxiliary voltage-gated calcium channel subunits and multiple voltage-gated potassium channel subunits, respectively. Our results provide the first evidence of agedependent coexpression of the largest group of clustered miRNAs in the Dlk1-Dio3 locus (at least 15 in mice and seven in humans) to inhibit a common atrophy-related gene target, Atrogin-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[59][60][61] Recent experiments have shown that coexpressed miRNA clusters consisting of three to six members can regulate a specific molecular pathway by targeting the same signalling pathway. 13,14 The miR-183 cluster (bearing miR-183,miR-96, and miR-182) and the miR-17-92 cluster (bearing miR-17,miR-18a,miR-19a, miR-19b, and miR-92a) controlled neuropathic pain by repressing auxiliary voltage-gated calcium channel subunits and multiple voltage-gated potassium channel subunits, respectively. Our results provide the first evidence of agedependent coexpression of the largest group of clustered miRNAs in the Dlk1-Dio3 locus (at least 15 in mice and seven in humans) to inhibit a common atrophy-related gene target, Atrogin-1.…”
Section: Discussionmentioning
confidence: 99%
“…9 MiRNAs are frequently arranged in polycistronic clusters and coexpressed at a specific genomic locus, showing a general tendency to cotarget the same complex or pathway. [10][11][12][13][14] We recently demonstrated that >50% of down-regulated miRNAs in aged mouse skeletal muscle and myoblasts are clustered in the delta-like homologue 1 and the type III iodothyronine deiodinase (Dlk1-Dio3) imprinted genomic region. [15][16][17] Dlk1-Dio3 is the largest known placental mammalian-specific miRNA cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the bioinformatic analysis showed a predicted interaction of RP11‐819C21.1 with 24 miRNAs and ZNRD1‐AS1 with 40 miRNAs. It is particularly interesting that both lncRNAs showed miR‐19a and miR19b as common target, since these miRNAs are involved in the modulation of multiple potassium channel α subunits and auxiliary subunits in DRG neurons of L5 SNL model of neuropathic pain (Sakai et al, ). Our data agree with Zhao and collaborators’ hypothesis, according to which the up‐regulation of Kcna2 antisense RNA reduces Kcna2 mRNA expression leading to diminished K + current in the injured DRG of rat model SNL (Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Since intrathecal miR-21 injection induces pain hypersensitivity in wild-type mice but not in mice with a global deletion of toll-like receptor 8 (Tlr8 −/− ), the TLR8 receptor appears to act as a downstream effector of miR-21 to maintain neuropathic pain; however, a direct targeting of the Tlr8 gene has not been validated yet [124]. miR-18, miR-19a, miR-19b as well as mir-92 are also up-regulated in neuropathic pain models and in turn down-regulate potassium channels including Kcna1, Kcna4, Kcnc4, Kcnd3 and Kcnq5 [73]. The suppression of potassium channels in general increases neuronal excitability and this may be a relevant mechanism causing nociceptor excitation and sensitization [125,126].…”
Section: Mirnas Deregulated In the Peripheral Nervementioning
confidence: 99%